Influence of Working Engagement of Those Convicted to Deprivation of Liberty - Petrović, Vera; Jovanić, Goran (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The aim of this paper is to determine the influence of the working engagement of convicts in the course of incarceration on the intensity of deprivation of freedom. The research was conducted in the Detention and Rehabilitation Centre Sremska Mitrovica. The study included 113 convicts who volunteered to participate in the research. The data on deprivation of freedom was obtained by applying the Freedom Deprivation Scale, whereas social-demographic, criminal and penal characteristics were collected by means of a questionnaire custom-made for the purpose of this research. The reliability of the freedom deprivation scale was determined to be very high (Cronbach's α = 0.92). The results of the research indicate the existence of a statistically significant difference between the convicts who were engaged in work in the course of their prison sentence and those who were not in terms of the Freedom Deprivation Scale score.